The trapping of live neutrophils by macrophages during infection - Kelley N. Cooper; Marina Terekhova; Barbara Potempa; Ana D’Aubeterre; Jerome Timbol; Si An Chen; Antoine Dufour; Shunying Jin; Maxim N. Artyomov; Jan Potempa; Juhi Bagaitkar (Cell Death and Disease)
Abstract Neutrophils are highly abundant in the oral mucosal tissues, and their balanced activation and clearance are essential for immune homeostasis. Here, we demonstrate that neutrophils infected with the bacterial pathogen Porphyromonas gingivalis (Pg) are captured alive by macrophages in a manner that bypasses all known receptor-ligand interactions involved in the phagocytosis of either live or dead cells. Mechanistically, upon interaction with Pg, or its protease RgpB (gingipains), live neutrophils undergo rapid remodeling of their proteomes, generating neoepitopes. N-terminomics-based proteomic profiling identified multiple RgpB cleavage sites on several azurophilic granule proteins that are translocated to the surface of live neutrophils via low-level degranulation and activate macrophage αMβ2 integrin receptors, thus mediating internalization of non-apoptotic neutrophils within macrophage phagosomes. Macrophages with entrapped live neutrophils exhibit phenotypic and transcriptional reprogramming, consistent with inflammatory outcomes in vitro and in vivo. In contrast to the immunosuppressive outcomes associated with efferocytosis of apoptotic neutrophils, live neutrophil entrapment failed to fully activate several catabolic and metabolic processes and exhibited a defective activation of PPAR-γ mediated pro-resolution pathways, thereby promoting bacterial persistence and hindering the resolution of inflammation. Thus, our data demonstrate a novel immune subversion strategy unique to Pg and reveal a previously unknown mode of live neutrophil sequestration into macrophages during an infection.